2009
DOI: 10.1038/nrd2781
|View full text |Cite
|
Sign up to set email alerts
|

Is NF-κB a good target for cancer therapy? Hopes and pitfalls

Abstract: Preface NF-κB transcription factors play a key role in many physiological processes, such as innate and adaptive immune responses, cell proliferation, cell death, and inflammation. It has become clear that aberrant regulation of NF-κB and the signaling pathways that control its activity are involved in cancer development and progression, as well as in resistance to chemo- and radiotherapy. This review discusses recent cancer-genetics and cancer-genome evidence for the involvement of NF-κB in human cancer, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
887
1
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 972 publications
(915 citation statements)
references
References 102 publications
15
887
1
12
Order By: Relevance
“…The molecular mechanisms underling this process have only recently started to be clarified with biochemical and genetic studies (95). The results of Pikarsky et al (8) , Greten et al (72) , and Luo et al (78) identified the NF-B signaling pathway could be regarded as a rational target for cancer therapy, and there is significant enthusiasm from cell culture experiments and animal models for the use of NF-B inhibitors as a new anti-cancer therapy in recent years (14,96,97). However, several questions remain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular mechanisms underling this process have only recently started to be clarified with biochemical and genetic studies (95). The results of Pikarsky et al (8) , Greten et al (72) , and Luo et al (78) identified the NF-B signaling pathway could be regarded as a rational target for cancer therapy, and there is significant enthusiasm from cell culture experiments and animal models for the use of NF-B inhibitors as a new anti-cancer therapy in recent years (14,96,97). However, several questions remain.…”
Section: Discussionmentioning
confidence: 99%
“…The pivotal role of the NF-B signaling pathway in apoptosis, tumor promotion and tumor maintenance, strongly suggests that NF-B inhibitors would be useful in cancer therapy, and much efforts is currently invested in developing NF-B inhibitors in cancers (10,14,85,86). Several agents have been implemented to inhibit IKK/NF-B activity, because of the relevance of this process in cancer and those related with inflammation, such as curcumin, ginseng extract, resveratrol, green tea extract have anti-inflammatory and antiproliferative propertiese (87).…”
Section: Nf-b Inhibition: Strategy For Colorectal Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…While normal activation of NF-B is required for cell survival and immunity, it is now well established that the deregulated activation of NF-B is associated with cancer, inflammation, and a wide range of other pathologies [3][4][5][6][7][8][9][10][11]. Because of its severe implications in a large number of diseases, NF-B has recently become a major target in drug discovery [4,7,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of NF-jB promotes transcription of a wide variety of genes, which are related to inflammation and tumor growth (Baud and Karin 2009). Many studies have shown that NF-jB plays a crucial role in the pathogenesis of esophageal adenocarcinoma (Abdel-Latif et al 2004;Konturek et al 2004;O'Riordan et al 2005).…”
Section: Gsk3b Affects Tumorigenesis Of Ec Through Transcription Factmentioning
confidence: 99%